An anthracene-containing organic electroluminescent material and an organic electroluminescent device thereof

CN117186131BActive Publication Date: 2026-10-27WUHAN SUNSHINE OPTOELECTRONICS TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310933980.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2026-10-27
Estimated Expiration
2043-07-27

AI Technical Summary

Technical Problem

而对于以N-B键形成的类萘小核心作为取代基构建半导体材料,并对化合物光电性能进行的研究则较少见,到现在为止,已公开的包含其的光电材料电流效率、光色和寿命方面的综合性能也都不符合产业标准,因而,市场上还没有一款含硼氮键的可用于商业化应用的有机电致发光材料

Benefits of technology

[0045](1)本发明与蒽9,10位点桥接,避免B的空P轨道受到亲核攻击,稳定性更好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117186131B_ABST
    Figure CN117186131B_ABST
Patent Text Reader

Abstract

The application discloses an anthracene-containing organic electroluminescent material and application thereof, and the structure of the material is shown as chemical formula 1: the bridging site of the anthracene group is adjacent to a B atom, so that the empty P orbital of the photoelectric material B formed by the boron-nitrogen bond is avoided from being subjected to nucleophilic attack, and the stability is better. The organic electroluminescent device prepared by using the compound disclosed by the application not only has good electron / hole transmission performance, but also can provide a higher electron / hole injection barrier and blocking effect, realizes high brightness, long service life and light color blue shift luminescence effect, and thus the performance and stability of the OLED device are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of optoelectronic materials application technology, specifically relating to an anthracene-containing organic electroluminescent material and its organic electroluminescent device. Technical Background

[0002] In recent years, organic light-emitting diodes (OLEDs) have been widely used in solid-state lighting and flat panel displays. Among them, novel π-conjugated organic unit materials containing co-intercalated organic boron and nitrogen have become a research hotspot in blue OLED material systems due to their excellent photophysical and electrochemical properties.

[0003] Among them, boron-nitrogen heterocyclic aromatic compounds possess highly efficient charge transport properties and can be used in devices such as organic light-emitting diodes and solar cells. Their structure consists of a six-membered ring containing boron and nitrogen linked to a six-membered ring containing carbon and hydrogen, forming a bicyclic structure similar to naphthalene. The electronic properties and molecular arrangement of these compounds can be tuned by using different substituents, thereby optimizing device performance.

[0004] In the prior art, research on aromatic compounds containing boron-nitrogen bonds mainly focuses on fused heterocyclic structures with polycyclic fused large conjugated structures as the core, such as...

[0005] (See patents CN110003260A and KR2017045426A for details). However, research on semiconductor materials constructed using N-B bond-formed naphthalene-like cores as substituents and on the photoelectric properties of these compounds is relatively rare. To date, the overall performance of publicly disclosed photoelectric materials containing these compounds in terms of current efficiency, color, and lifetime does not meet industry standards. Therefore, there is currently no commercially available organic electroluminescent material containing boron-nitrogen bonds. This application aims to precisely design and control the compound structure of boron-nitrogen-based organic electroluminescent materials for industrialization, thereby ensuring that their overall performance in terms of efficiency roll-off, luminous efficiency, and lifetime meets the performance requirements of panel production lines, accelerating the commercial application of boron-based materials. Summary of the Invention

[0006] To address the aforementioned technical problems, this invention provides an anthracene-containing organic electroluminescent material and its organic electroluminescent device.

[0007] An anthracene-containing organic electroluminescent material has the structure shown in Chemical Formula 1:

[0008]

[0009] Wherein, L1 and L2 are each independently selected from one of: single bond, phenylene, biphenylene, and naphthylene, wherein the phenylene is selected from unsubstituted or C1-C 12 alkane group, C1-C 12 The alkoxy, nitro, or cyano-substituted phenylene groups, wherein the phenylene groups are selected from unsubstituted or C1-C6 groups. 12 alkane group, C1-C 12 The alkoxy, nitro, or cyano-substituted biphenylene, wherein the naphthyl group is selected from unsubstituted or C1-C6 groups. 12 alkane group, C1-C 12 Alkoxy, nitro, or cyano-substituted naphthyl groups;

[0010] Ar1 is an electron-donating or electron-deficient group, selected from: optionally substituted C6-C 30 aryl, optionally substituted C3-C 30 Mixed aromatic compounds.

[0011] As a preferred technical solution, the C6-C 30 The aryl group is selected from: phenyl, biphenyl, triphenyl

[0012] Biphenyl, naphthyl, naphthylphenyl, phenylnaphthyl, anthracene, phenanthrene, diphenylamino, 9,9-dimethylfluorenyl; the optionally substituted C6-C 30 The heteroaryl group is selected from: pyridinyl, pyrimidinyl, 1,3,5-triazinyl, benzoxazolyl, benzothiazolyl, benzoimidazolyl, dibenzofuranyl, dibenzothiophenyl, carbazolyl, phenylcarbazolyl, carbazolylphenyl, naphthobenzofuranyl, naphthobenzothiophenyl, benzocarbazolyl, diphenylphospho, diphenylphosphoxy.

[0013] As a preferred technical solution, Ar1 is a C6-C substituent substituted with the following substituents. 30 aryl or C3-C 30 One of the heteroaryl groups, wherein the substituent is selected from: H, nitro, cyano, C1-C4 alkyl, C1-C4 alkoxy, phenyl, naphthyl, biphenyl, terphenyl, carbazole, diphenylamino.

[0014] As a preferred technical solution, Ar1 is selected from one of the following A1-A7:

[0015]

[0016] Q1 is selected from N(Y1), O, S, C(Y2)(Y3);

[0017] Q2 is selected from N, P, and P=O;

[0018] Ar2 indicates that it is absent or is a monocyclic aromatic hydrocarbon, wherein the Ar2 is directly fused with the connected naphthalene ring;

[0019] Z1 is independently selected from CH, C or N, and N is 1 to 3 non-adjacent ones, that is, N is 1, 2 or 3 and they are not adjacent to each other;

[0020] Y1, Y2, and Y3 are each independently selected from: H, C1-C4 alkyl, cyano, C1-C4 alkoxy, and phenyl, wherein the phenyl group is selected from unsubstituted or substituted phenyl groups of C1-C4 alkyl, cyano, or C1-C4 alkoxy.

[0021] R1-R9 have the same meaning as the substituents in Ar1 mentioned above;

[0022] * indicates the site that bridges with L2.

[0023] As a preferred technical solution, the Selected from: This can be further expressed as:

[0024] This can be further expressed as:

[0025] Among them, at least one of Z1 is N, and the rest are CH.

[0026] As a preferred technical solution, the This can be further expressed as:

[0027]

[0028] The This can be further expressed as:

[0029] The This can be further expressed as:

[0030]

[0031] The This can be further expressed as:

[0032] The This can be further expressed as:

[0033] The This can be further expressed as:

[0034] As a preferred technical solution, when Ar1 is an electron-donating group, it is selected from A1, A2, A3, A4, and A5, wherein Z1 in A1 and A4 is C(Y2) or C, and Q2 in A5 is P or P=O; when Ar1 is an electron-deficient group, it is selected from A1, A4, A5, A6, and A7, wherein at least one Z1 in A1 and A4 is N, and Q2 in A5 is N.

[0035] The following are specific examples of chemical formula 1, but are not limited to these.

[0036]

[0037]

[0038]

[0039]

[0040]

[0041] A second aspect of the present invention provides an organic electroluminescent device comprising a first electrode; a second electrode; and an organic layer disposed between the first electrode and the second electrode, the organic layer comprising an organic electroluminescent material represented by Formula 1.

[0042] Furthermore, the organic layer comprises: a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, and an electron injection layer.

[0043] At least one of the light-emitting layer or electron transport layer contains the anthracene-containing organic electroluminescent material provided by the present invention.

[0044] This invention provides an anthracene-containing organic electroluminescent material and its organic electroluminescent device. Compared with the prior art, this invention has the following advantages and beneficial effects:

[0045] (1) The present invention is bridged with the 9 and 10 sites of anthracene to avoid nucleophilic attacks on the empty P orbitals of B, resulting in better stability.

[0046] (2) When this invention is used as a fluorescent or phosphorescent material in the OLED light-emitting layer, it can achieve high brightness, blue shift of light color and long lifespan light emission effect.

[0047] (3) When used as a transport material, this invention not only has good electron transport or hole transport performance, but also provides a high electron / hole injection barrier and blocking effect, thereby improving the performance and stability of OLED devices. Detailed Implementation

[0048] It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.

[0049] Intermediate: Compound T-1

[0050]

[0051] In a 500 mL reaction flask, A-1 (6.76 g, 25 mmol), pinacol diborate (6.35 g, 32.5 mmol), 1,1'-bis(diphenylphosphine)ferrocene (0.14 g, 0.25 mmol), potassium acetate (4.91 g, 50 mmol), and 100 mL of toluene were added. The mixture was heated to 120 °C under a nitrogen atmosphere. After the reaction was completed by liquid phase monitoring, the mixture was cooled to 90 °C and passed through a silica gel Buchner funnel while hot. Crystallization was performed using ethyl acetate, filtered at room temperature, and recrystallized with 4 times the volume of ethylamine. The crystals were dried to obtain 5.03 g of Y-1, with a yield of 79%.

[0052] In a 250 mL reaction flask, compounds Y-1 (3.82 g, 15 mmol), Y-2 (5.7 g, 16.95 mmol), tris(dibenzylacetone)palladium (0.69 g, 0.75 mmol), sodium carbonate aqueous solution (2 M, 20 mL), ethanol (20 mL), and toluene (50 mL) were added. Under a nitrogen atmosphere, the mixture was heated to 90 °C, stirred, and monitored by liquid chromatography until the reaction endpoint was reached. The mixture was then cooled, water was added, and the mixture was allowed to stand and separate. The aqueous phase was extracted once with ethyl acetate, and the extracts were combined with the organic phase. The mixture was dried and concentrated to obtain a large amount of solid, which was purified with tetrahydrofuran and petroleum ether to give compound T-1 (4.9 g), with a yield of 85%. The molecular weight was determined to be 383.05 by MALDI TOF MS, confirming it as the target compound T-1.

[0053] Intermediate: Compound T-2

[0054]

[0055] In a 500 mL reaction flask, T-1 (9.6 g, 25 mmol), pinacol diborate (8.25 g, 32.5 mmol), 1,1'-bis(diphenylphosphine)ferrocene (0.14 g, 0.25 mmol), potassium acetate (4.91 g, 50 mmol), and 100 mL of toluene were added. The mixture was heated to 120 °C under a nitrogen atmosphere. After the reaction was completed by liquid phase monitoring, the temperature was lowered to 90 °C. The mixture was passed through a silica gel Buchner funnel while hot and crystallized with ethyl acetate. After filtration at room temperature, 4 times the volume of ethylamine was added to the solid phase for recrystallization. The solid phase was dried to obtain 8.38 g of Y-3, with a yield of 77.7%.

[0056] In a 250 mL reaction flask, compound Y-3 (6.47 g, 15 mmol), p-dibromobenzene (4.0 g, 16.95 mmol), tris(dibenzylacetone)dipalladium (0.69 g, 0.75 mmol), sodium carbonate aqueous solution (2 M, 20 mL), ethanol (20 mL), and toluene (50 mL) were added. Under a nitrogen atmosphere, the mixture was heated to 90 °C, stirred, and monitored by liquid chromatography until the reaction endpoint was reached. The mixture was cooled, water was added, and the mixture was allowed to stand and separated. The aqueous phase was extracted once with ethyl acetate, and the extracts were combined with the organic phase. The extracts were dried, concentrated, and a large amount of solid was obtained. The solid was purified with tetrahydrofuran and petroleum ether to give compound T-2 (5.77 g), with a yield of 83.6%. The molecular weight was determined to be 459.08 by MALDI TOF MS, confirming it as the target compound T-2.

[0057] Intermediate: Compound T-3

[0058]

[0059] In a 250 mL reaction flask, compounds Y-1 (3.82 g, 15 mmol), Y-4 (8.82 g, 16.95 mmol), tris(dibenzylacetone)palladium (0.69 g, 0.75 mmol), sodium carbonate aqueous solution (2 M, 20 mL), ethanol (20 mL), and toluene (50 mL) were added. Under a nitrogen atmosphere, the mixture was heated to 90 °C, stirred, and monitored by liquid chromatography until the reaction endpoint was reached. The mixture was cooled, water was added, and the mixture was allowed to stand and separated. The aqueous phase was extracted once with ethyl acetate, and the extracts were combined with the organic phase. The mixture was dried and concentrated to obtain a large amount of solid, which was purified with tetrahydrofuran and petroleum ether to give compound T-3 (7.01 g), with a yield of 87.1%. The molecular weight was determined to be 536.28 by MALDI TOF MS, confirming it as the target compound T-3.

[0060] Intermediate: Compound T-4

[0061]

[0062] In a 500 mL reaction flask, compound Y-1 (7.65 g, 30 mmol), p-dibromobenzene (8 g, 33.9 mmol), tris(dibenzylacetone)dipalladium (1.3 g, 1.5 mmol), sodium carbonate aqueous solution (2 M, 40 mL), ethanol (40 mL), and toluene (100 mL) were added. Under a nitrogen atmosphere, the mixture was heated to 90 °C, stirred, and monitored by liquid phase until the reaction endpoint was reached. The mixture was cooled, water was added, and the mixture was allowed to stand and separated. The aqueous phase was extracted once with ethyl acetate, and the extracts were combined with the organic phase. The mixture was dried and concentrated to obtain a large amount of solid, which was purified with tetrahydrofuran and petroleum ether to give compound Y-4 (6.83 g), with a yield of 80.2%.

[0063] Compound Y-4 (7.1 g, 25 mmol), pinacol diborate (8.25 g, 32.5 mmol), 1,1'-bis(diphenylphosphine)ferrocene (0.14 g, 0.25 mmol), potassium acetate (4.91 g, 50 mmol), and 100 mL of toluene were added to a 500 mL reaction flask. The mixture was heated to 120 °C under a nitrogen atmosphere. The reaction was monitored by liquid phase until completion. The mixture was then cooled to 90 °C and passed through a silica gel Buchner funnel while hot. Crystallization was performed using ethyl acetate, filtered at room temperature, and recrystallized with 4 times the volume of ethylamine. The crystals were dried to obtain 5.97 g of compound Y-5, with a yield of 72.1%.

[0064] In a 250 mL reaction flask, compound Y-5 (4.97 g, 15 mmol), compound Y-2 (5.7 g, 16.95 mmol), tris(dibenzylacetone)dipalladium (0.69 g, 0.75 mmol) sodium carbonate aqueous solution (2 M, 20 mL), ethanol (20 mL), and toluene (50 mL) were added. Under a nitrogen atmosphere, the mixture was heated to 90 °C, stirred, and monitored by liquid chromatography until the reaction endpoint was reached. The mixture was cooled, water was added, and the mixture was allowed to stand and separated. The aqueous phase was extracted once with ethyl acetate, and the extracts were combined with the organic phase. The mixture was dried and concentrated to obtain a large amount of solid. The solid was purified with tetrahydrofuran and petroleum ether to obtain compound T-4 (4.9 g), with a yield of 85%. The molecular weight was determined to be 459.08 by mass spectrometry (MALDI-TOF-MS), confirming it as the target compound T-4.

[0065] Intermediate: Compound T-5

[0066]

[0067] In a 250 mL reaction flask, compound Y-3 (6.47 g, 15 mmol), 2,5-dimethyl-4-bromoiodobenzene (5.27 g, 16.95 mmol), tris(dibenzylacetone)dipalladium (0.69 g, 0.75 mmol), sodium carbonate aqueous solution (2 M, 20 mL), ethanol (20 mL), and toluene (50 mL) were added. Under a nitrogen atmosphere, the mixture was heated to 90 °C, stirred, and monitored by liquid chromatography until the reaction endpoint was reached. The mixture was cooled, water was added, and the mixture was allowed to stand and separated. The aqueous phase was extracted once with ethyl acetate, and the extracts were combined with the organic phase. The mixture was dried and concentrated to obtain a large amount of solid, which was purified with tetrahydrofuran and petroleum ether to give compound T-5 (6.16 g), with a yield of 84.1%. The molecular weight was determined by MALDI-TOF-MS to be 487.11, confirming it as the target compound T-5.

[0068] Example 1: Synthesis of compound 1-1

[0069]

[0070] In a 250 mL reaction flask, compound T-1 (1.92 g, 5 mmol), compound S-1 (1.44 g, 5.65 mmol), tris(dibenzylacetone)dipalladium (0.23 g, 0.25 mmol), sodium carbonate aqueous solution (2 M, 20 mL), ethanol (20 mL), and toluene (50 mL) were added. Under a nitrogen atmosphere, the mixture was heated to 90 °C, stirred, and the reaction was monitored until the endpoint was reached. The mixture was cooled, water was added, and the mixture was allowed to stand and separated. The aqueous phase was extracted once with ethyl acetate, and the extracts were combined with the organic phase. The mixture was concentrated and purified by column chromatography with a 1:10 dichloromethane and petroleum ether solution to obtain compound 1-1 (1.92 g), with a yield of 89%.

[0071] Mass spectrometer: MALDI TOF MS (m / z) = 431.68, theoretical molecular weight: 431.18, elemental analysis: theoretical value: C 33 H 22 N (%): C, 89.11; H, 5.14; N, 3.25; Measured values: C, 89.09; H, 5.15; N, 3.23.

[0072] Example 2: Synthesis of compounds 1-2

[0073]

[0074] By replacing compound T-1 with compound T-2 (2.30 g, 5 mmol) and compound S-1 with compound S-2 (1.72 g, 5.65 mmol) in Example 1, and following the steps in 1-1, compound 1-2 (2.43 g) was obtained with a yield of 87.1%.

[0075] Mass spectrometer: MALDI TOF MS (m / z) = 578.31, theoretical molecular weight: 577.23, elemental analysis: theoretical value: C 42 H 28 N (%): C, 90.49; H, 5.06; N, 2.51; Measured values: C, 90.46; H, 5.09; N, 2.54.

[0076] Example 3: Synthesis of compounds 1-3

[0077]

[0078] In Synthesis Example 1, compound T-1 was replaced with compound T-2 (2.30 g, 5 mmol), and compound S-1 was replaced with compound S-3 (2.01 g, 5.65 mmol). The rest of the synthesis process was carried out according to step 1-1 to obtain compound 1-3 (2.68 g) with a yield of 88%.

[0079] Mass spectrometer: MALDI TOF MS (m / z) = 608.73, theoretical molecular weight: 609.26, elemental analysis: theoretical value: C 46 H 32 N (%): C, 90.64; H, 5.29; N, 2.30; Measured values: C, 90.66; H, 5.29; N, 2.29.

[0080] Example 4: Synthesis of compounds 1-4

[0081]

[0082] By replacing compound T-1 with compound T-2 (2.30 g, 5 mmol) and compound S-1 with compound S-4 (2.03 g, 5.65 mmol) in Example 1, and following the steps in 1-1, compound 1-4 (2.60 g) was obtained with a yield of 84.9%.

[0083] Mass spectrometer: MALDI TOF MS (m / z) = 612.48, theoretical molecular weight: 612.25, elemental analysis: theoretical value: C 43 H 29 N4 (%): C, 84.32; H, 4.77; N, 9.15; Measured values: C 84.31; H, 4.77; N, 9.17.

[0084] Example 5: Synthesis of compounds 1-5

[0085]

[0086] By replacing compound S-1 in Example 1 with compound S-5 (1.81 g, 5.65 mmol) and following the steps in 1-1, compound 1-5 (2.15 g) was obtained with a yield of 86.5%.

[0087] Mass spectrometer: MALDI TOF MS (m / z) = 498.17, theoretical molecular weight: 497.23, elemental analysis: theoretical value: C 37 H 28 N (%): C, 89.34; H, 5.67; N, 2.82; Measured values: C, 89.34; H, 5.65; N, 2.86.

[0088] Example 6: Synthesis of compounds 1-6

[0089]

[0090] By replacing compound T-1 with compound T-2 (2.30 g, 5 mmol) and compound S-1 with compound S-6 (1.66 g, 5.65 mmol) in Example 1, and following the steps in 1-1, compound 1-6 (2.15 g) was obtained with a yield of 86.5%.

[0091] Mass spectrometer: MALDI TOF MS (m / z) = 546.77, theoretical molecular weight: 547.21, elemental analysis: theoretical value: C 40 H 26 N (%): C, 87.76; H, 4.79; N, 2.56; Measured values: C, 87.74; H, 4.80; N, 2.56.

[0092] Example 7: Synthesis of compounds 1-7

[0093]

[0094] In a reaction flask, compounds T-2 (2.30 g, 5 mmol), S-7 (1.77 g, 5.25 mmol), tris(dibenzyleneacetone)palladium (0.23 g, 0.25 mmol), 4,5-bis(diphenylphosphine-9,9-dimethyloxanthracene) (0.29 g, 0.5 mmol), sodium tert-butoxide (0.96 g, 10 mmol), and 10V toluene were added. The mixture was stirred and heated to 120°C under nitrogen atmosphere. The reaction was monitored by liquid phase until completion. The mixture was cooled, water was added, and the product was filtered at room temperature. The product was dissolved in 10V toluene by heating, and the solution was passed through silica gel while hot. The filtrate was collected, concentrated, and crystallized in ethanol for 1.5 h. After filtration and drying, the product 1-7 (2.79 g) was obtained, with a yield of 78.1%.

[0095] Mass spectrometer: MALDI TOF MS (m / z) = 716.04, theoretical molecular weight: 715.32, elemental analysis: theoretical value: C 52 H 38 N3 (%): C, 87.27; H, 5.35; N, 5.87; Measured values: C, 87.29; H, 5.33; N, 5.87.

[0096] Example 8: Synthesis of compounds 1-8

[0097]

[0098] By replacing compound T-1 with compound T-2 (2.30 g, 5 mmol) and compound S-1 with compound S-8 (2.28 g, 5.65 mmol) in Example 1, and following the steps in 1-1, compound 1-8 (2.45 g) was obtained with a yield of 84.2%.

[0099] Mass spectrometer: MALDI TOF MS (m / z) = 581.65, theoretical molecular weight: 581.21, elemental analysis: theoretical value: C 40 H 29 N (%): C, 82.63; H, 5.03; N, 2.41; Measured values: C, 82.63; H, 5.01; N, 2.43.

[0100] Example 9: Synthesis of compounds 1-9

[0101]

[0102] In Synthesis Example 7, compound T-2 was replaced with compound T-1 (1.66 g, 5.65 mmol), and compound S-7 was replaced with compound S-9 (1.05 g, 5.25 mmol). The rest of the synthesis process was carried out according to steps 1-7, and compounds 1-9 (2.03 g) were obtained with a yield of 86.2%.

[0103] Mass spectrometer: MALDI TOF MS (m / z) = 470.09, theoretical molecular weight: 470.20, elemental analysis: theoretical value: C 34 H 23 N2 (%): C, 86.82; H, 4.93; N, 5.96; Measured values: C, 86.80; H, 4.94; N, 5.96.

[0104] Example 10: Synthesis of compounds 1-10

[0105]

[0106] In Example 7, compound T-2 was replaced with compound T-1 (1.92 g, 5 mmol), and compound S-7 was replaced with compound S-10 (0.89 g, 5.25 mmol). The rest of the synthesis process was carried out according to steps 1-7 to obtain compounds 1-9 (1.99 g) with a yield of 84.1%.

[0107] Mass spectrometer: MALDI TOF MS (m / z) = 472.21, theoretical molecular weight: 472.19, elemental analysis: theoretical value: C 32 H 21 N4 (%): C, 81.37; H, 4.48; N, 11.86; Measured values: C, 81.37; H, 4.49; N, 11.88.

[0108] Example 11: Synthesis of compounds 1-11

[0109]

[0110] By replacing compound S-1 in Synthesis Example 1 with compound S-11 (1.38 g, 5.65 mmol) and following the steps in 1-1, compound 1-11 (1.77 g) was obtained with a yield of 83.7%.

[0111] Mass spectrometer: MALDI TOF MS (m / z) = 421.91, theoretical molecular weight: 422.16, elemental analysis: theoretical value: C 29 H 19 N2 (%): C, 82.48; H, 4.54; N, 6.63; Measured values: C, 82.44; H, 4.56; N, 6.66.

[0112] Example 12: Synthesis of compounds 1-12

[0113]

[0114] By replacing compound T-1 in synthesis example 1 with compound T-3 (2.68 g, 5 mmol) and following the steps in 1-1, compound 1-12 (2.33 g) was obtained with a yield of 80%.

[0115] Mass spectrometer: MALDI TOF MS (m / z) = 582.72, theoretical molecular weight: 583.25, elemental analysis: theoretical value: C 44 H 30 N (%): C, 90.57; H, 5.18; N, 2.40; Measured values: C, 90.57; H, 5.18; N, 2.41.

[0116] Example 13: Synthesis of compounds 1-13

[0117]

[0118] By replacing compound S-7 in synthesis example 7 with compound S-13 (0.78 g, 5.25 mmol) and following the steps in 1-7, compound 1-13 (2.15 g) was obtained with a yield of 82%.

[0119] Mass spectrometer: MALDI TOF MS (m / z) = 525.38, theoretical molecular weight: 525.24, elemental analysis: theoretical value: C 37 H 28 N3 (%): C, 84.57; H, 5.37; N, 8.00; Measured values: C, 84.51; H, 5.40; N, 8.01.

[0120] Example 14: Synthesis of compounds 1-14

[0121]

[0122] By replacing compound T-1 with compound T-3 (2.68 g, 5 mmol) and compound S-1 with compound S-6 (1.66 g, 5.65 mmol) in Synthesis Example 1, and following the steps in 1-1, compound 1-14 (2.45 g) was obtained with a yield of 78.7%.

[0123] Mass spectrometer: MALDI TOF MS (m / z) = 623.42, theoretical molecular weight: 623.24, elemental analysis: theoretical value: C 46 H 30 N (%): C, 88.60; H, 4.85; N, 2.25; Measured values: C, 88.61; H, 4.85; N, 2.25.

[0124] Example 15: Synthesis of compounds 1-15

[0125]

[0126] In Synthesis Example 7, compound T-2 was replaced with compound T-4 (1.92 g, 5 mmol), and compound S-7 was replaced with compound S-10 (0.89 g, 5.25 mmol). The rest of the synthesis process was carried out according to steps 1-7, and compound 1-15 (2.28 g) was obtained with a yield of 83.1%.

[0127] Mass spectrometer: MALDI TOF MS (m / z) = 548.51, theoretical molecular weight: 548.22, elemental analysis: theoretical value: C 38 H 25 N4 (%): C, 83.22; H, 4.59; N, 10.22; Measured values: C, 83.23; H, 4.59; N, 10.22.

[0128] Example 16: Synthesis of compounds 1-16

[0129]

[0130] In Synthesis Example 1, compound T-1 was replaced with compound T-5 (2.82 g, 5 mmol), and compound S-1 was replaced with compound S-16 (1.67 g, 5.65 mmol). The rest of the synthesis process was carried out according to step 1-1, and compound 1-16 (2.41 g) was obtained with a yield of 73.8%.

[0131] Mass spectrometer: MALDI TOF MS (m / z) = 652.53, theoretical molecular weight: 652.30, elemental analysis: theoretical value: C 48 H37 N2 (%): C, 88.34; H, 5.71; N, 4.29; Measured values: C, 88.36; H, 5.70; N, 4.29.

[0132] Example 17: Synthesis of compounds 1-17

[0133]

[0134] In Synthesis Example 1, compound T-1 was replaced with compound T-2 (2.30 g, 5 mmol), and compound S-1 was replaced with compound S-17 (1.44 g, 5.65 mmol). The rest of the synthesis process was carried out according to step 1-1 to obtain compound 1-17 (2.24 g) with a yield of 88.3%.

[0135] Mass spectrometer: MALDI TOF MS (m / z) = 507.13, theoretical molecular weight: 507.22, elemental analysis: theoretical value: C 38 H 26 N (%): C, 89.94; H, 5.16; N, 2.76; Measured values: C, 88.36; H, 5.70; N, 4.29.

[0136] Example 18 Fabrication of Device 1

[0137] The glass substrate with a 120nm ITO transparent film was ultrasonically cleaned with acetone, isopropanol and deionized water for 10 minutes each, vacuum dried at 105°C for 2 hours, and then UV ozone washed for 15 minutes. The ITO glass substrate was then transferred to a vacuum evaporation machine.

[0138] On the side where the ITO thin film is formed, molybdenum trioxide (MoO3) is vacuum-deposited to form a 10 nm thick hole injection layer.

[0139] Next, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB) is vacuum-deposited onto the hole injection layer to form a 70 nm thick hole transport layer.

[0140] Next, on the hole transport layer, compound 1-1 (as the luminescent host material, 90 wt%) and 4,4'-bis(9-ethyl-3-carbazole vinyl)-1,1'-biphenyl (BCzVBi) (as the luminescent guest material, 10 wt%) prepared in the above synthesis example 1 are vacuum-deposited together to form a luminescent layer with a thickness of 30 nm.

[0141] Next, 3,3'-[5'-[3-(3-pyridyl)phenyl][1,1':3',1''-terphenyl]-3,3''-diyl]dipyridine (TmPyPB) is vacuum-deposited onto the aforementioned light-emitting layer to form an electron transport layer with a thickness of 40 nm.

[0142] Next, lithium fluoride (LiF) is vacuum-deposited on the electron transport layer to form an electron injection layer with a thickness of 1 nm; finally, aluminum (Al) is vacuum-deposited on the electron injection layer to form a cathode with a thickness of 100 nm, thus fabricating device 1.

[0143] Fabrication of Devices 2-17 in Examples 19-33

[0144] Organic electroluminescent devices were prepared using the same method as in Example 18, except that compounds synthesized in Examples 2 to 16 were used to replace compound 1-1, and the resulting devices were devices 2 to 17.

[0145] Fabrication of devices 18-20 in Comparative Examples 1-3

[0146] Organic electroluminescent devices were prepared using the same method as in Example 18, except that compound 1-1 was replaced with compounds D1, D2, and D3 respectively. The resulting devices are devices 18 to 20. The structures of D1, D2, and D3 are shown below:

[0147]

[0148] The performance of the organic electroluminescent devices fabricated using the above-mentioned devices was tested, and the results are shown in Table 1:

[0149] Table 1. Performance test results of devices prepared in Examples 18-33 and Comparative Examples 1-3

[0150]

[0151]

[0152] As can be seen from the data in Table 1 above, compared with the comparative example, the present invention bridges the anthracene at sites 9 and 10, avoiding nucleophilic attacks on the empty P orbitals of B, resulting in better stability. The introduction of different types of electron donor and acceptor groups allows for precise control of the electron and hole balance of the compound, achieving pure standard blue light emission. Furthermore, the device shows significant improvements in overall performance such as driving voltage, current efficiency, and lifespan, effectively solving the problems of high driving voltage and low fluorescence quantum efficiency in current organic electroluminescent devices due to difficulties in charge injection into the host material.

[0153] Example 34 Fabrication of Device 21

[0154] The glass substrate with a 120nm ITO transparent film was ultrasonically cleaned with acetone, isopropanol and deionized water for 10 minutes each, vacuum dried at 105°C for 2 hours, and then UV ozone washed for 15 minutes. The ITO glass substrate was then transferred to a vacuum evaporation machine.

[0155] On the side where the ITO thin film is formed, molybdenum trioxide (MoO3) is vacuum-deposited to form a 10 nm thick hole injection layer.

[0156] Next, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB) is vacuum-deposited onto the hole injection layer to form a 70 nm thick hole transport layer.

[0157] Next, 9,10-bis(2-naphthyl)anthracene (ADN) (as the luminescent host material, 90 wt%) and 4,4'-bis(9-ethyl-3-carbazole vinyl)-1,1'-biphenyl (BCzVBi) (as the luminescent guest material, 10 wt%) are co-vacuum-deposited on the aforementioned hole transport layer to form a luminescent layer with a thickness of 30 nm.

[0158] Next, on the above-mentioned light-emitting layer, compounds 1-4 prepared in the above-mentioned synthesis example 4 are vacuum evaporated to form an electron transport layer with a thickness of 40 nm.

[0159] Next, lithium fluoride (LiF) is vacuum-deposited onto the aforementioned electron transport layer to form an electron injection layer with a thickness of 1 nm.

[0160] Finally, aluminum (Al) is vacuum-deposited onto the aforementioned electron injection layer to form a 100 nm cathode, thus fabricating device 21.

[0161] Fabrication of Devices 22-27 in Examples 35-40

[0162] Organic electroluminescent devices were prepared using the same method as in Example 34, except that compounds 1-4 in Example 34 were replaced with compounds synthesized in Examples 8, 10, 11, 13, and 15, and compound (D1) in Comparative Example 1. The resulting devices were devices 22-27.

[0163] The performance of the organic electroluminescent devices prepared in the above-described device embodiments was tested, and the results are shown in Table 2:

[0164] Table 2. Performance test results of the devices prepared in Examples 34-40

[0165]

[0166] As can be seen from the data in Table 2 above, the organic optoelectronic material constructed by the present invention, which uses a naphthalene-like small molecule composed of B-N bonds to bridge the 9-position of anthracene and uses an electron-transporting group to cap the 10-position of anthracene, has a higher electron mobility than the device prepared using D1 compound. It also effectively reduces the electron injection energy barrier and significantly improves the performance of the device in terms of driving voltage and current efficiency.

Claims

1. An anthracene-containing organic electroluminescent material, characterized in that, The anthracene-containing organic electroluminescent material has the structure shown in Chemical Formula 1: Chemical Formula 1 Among them, L1 and L2 are independently selected from one of the following: single bond, phenylene, and methyl-substituted phenylene; Ar1 is an electron-donating group or an electron-deficient group; The Ar1 is selected from one of the following A1-A7: 、 、 、 、 、 、 ; Wherein, Q1 is selected from N(Y1), O, S, C(Y2)(Y3); Q2 is selected from N, P, and P=O; Ar2 indicates that it is absent or is a monocyclic aromatic hydrocarbon, wherein the Ar2 is directly fused with the connected naphthalene ring; Z1 is independently selected from CH, C or N. When Z1 contains N, N is 1, 2 or 3 and they are not adjacent to each other. Y1, Y2, and Y3 are each independently selected from: H, C1-C4 alkyl, cyano, C1-C4 alkoxy, and phenyl, wherein the phenyl is selected from unsubstituted or substituted phenyl by C1-C4 alkyl, cyano, or C1-C4 alkoxy. Substituents R1-R9 are selected from: H, nitro, cyano, C1-C4 alkyl, C1-C4 alkoxy, phenyl, naphthyl, biphenyl, terphenyl, carbazolyl, and diphenylamino. * indicates the site that bridges with L2.

2. The anthracene-containing organic electroluminescent material according to claim 1, characterized in that, The Selected from: , ; This can be further expressed as: , , , , , , ; This can be further expressed as: , , , , , , ; Among them, at least one of Z1 is N, and the rest are CH.

3. The anthracene-containing organic electroluminescent material according to claim 1, characterized in that, The This can be further expressed as: , , , , ; The This can be further expressed as: , , , , , , , , , , , , , , , , , , ; The This can be further expressed as: , , , , , , , , ; The This can be further expressed as: , , , , , , , , , , , , ; The This can be further expressed as: , , , ; The This can be further expressed as: , , , .

4. An organic electroluminescent device, comprising: The first electrode, the second electrode, and the organic layer prepared between the first electrode and the second electrode are characterized in that the organic layer comprises the anthracene-containing organic electroluminescent material according to any one of claims 1 to 3.

5. An organic electroluminescent device according to claim 4, characterized in that, The organic layer comprises: a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, and an electron injection layer, wherein at least one of the light-emitting layer or electron transport layer contains the anthracene-containing organic electroluminescent material as described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Boron heterocyclic compounds, display panel and display device

    CN110003260A

  • Azaboradibenzochrysene derivatives organic electroluminescent compound, ink composition and organic electroluminescent device

    KR1020170045426A

  • Organic compound containing aza-boron group and application thereof

    CN115651004A

  • Boron-nitrogen polyaromatic compounds and their use in oleds

    US20140027734A1